Novel Composite Endpoint for Assessing Outcomes in Liver Transplantation: Arterial and Biliary Complication–Free Survival. Issue 1 (7th September 2021) - Savier, Eric; De Rycke, Yann; Lim, Chetana; Goumard, Claire; Rousseau, Geraldine; Perdigao, Fabiano; Rufat, Pierre; Salloum, Chady; Llado, Laura; Ramos, Emilio; Lopez‐Dominguez, Josefina; Cachero, Alba; et al.
Abstract : Transplant and patient survival are the validated endpoints to assess the success of liver transplantation (LT). This study evaluates arterial and biliary complication–free survival (ABCFS) as a new metric. ABC, considered as an event, was an arterial or biliary complication of Dindo‐Clavien grade ≥III complication dated at the interventional, endoscopic, or surgical treatment required to correct it. ABCFS was defined as the time from the date of LT to the dates of first ABC, death, relisting, or last follow‐up (transplant survival is time from LT to repeat LT or death). Following primary whole LT (n = 532), 106 ABCs occurred and 99 (93%) occurred during the first year after LT. An ABC occurring during the first year after LT (overall rate 19%) was an independent factor associated with transplant survival (hazard ratio [HR], 3.17; P < 0.001) and patient survival (HR, 2.7; P = 0.002) in univariate and multivariate analyses. This result was confirmed after extension of the cohort to split‐liver graft, donation after circulatory death, or re‐LT (n = 658). Data from 2 external cohorts of primary whole LTs (n = 249 and 229, respectively) confirmed that the first‐year ABC was an independent prognostic factor for transplant survival but not for patient survival. ABCFS was correlated with transplant and patient survival ( ρ = 0.85 [95% CI, 0.78‐0.90] and 0.81 [95% CI, 0.71‐0.88], respectively). Preoperative factors known to influence 5‐year transplant survival influenced ABCFS after 1 year of follow‐up. The 1‐year ABCFS was indicative of 5‐year transplant survival. ABCFS is a reproducible metric to evaluate the results of LT after 1 year of follow‐up and could serve as a new endpoint in clinical trials.